2003
DOI: 10.1007/s00330-003-1916-6
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic localization of occult pulmonary nodules during video-assisted thoracic surgery

Abstract: The aim of our study was to evaluate the role of ultrasonography in the localization of pulmonary nodules during video-assisted thoracic surgery (VATS). Ultrasonography was performed in 35 patients for the localization of pulmonary nodules during VATS. Indication for VATS was excisional biopsy of undetermined nodules in 22 patients, single or multiple metastasectomy in 12 patients and resection of primitive pulmonary cancer in 1 patient with reduced pulmonary reserve. A laparoscopic probe with flexible head an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 17 publications
3
37
3
Order By: Relevance
“…Although most studies report the actual ultrasound procedure time to be quite low, the time to deflate the lung can be quite lengthy in patients with emphysematous lungs, and many patients who have small pulmonary nodules fall into this group (41,42). In one series, ultrasonography wasn't attempted until the lung had been excluded from ventilation for at least 40 min (43). Also, there is a learning curve associated with use of the ultrasound equipment, with some studies reporting the presence of a radiologist in the operating room (38,43,44).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although most studies report the actual ultrasound procedure time to be quite low, the time to deflate the lung can be quite lengthy in patients with emphysematous lungs, and many patients who have small pulmonary nodules fall into this group (41,42). In one series, ultrasonography wasn't attempted until the lung had been excluded from ventilation for at least 40 min (43). Also, there is a learning curve associated with use of the ultrasound equipment, with some studies reporting the presence of a radiologist in the operating room (38,43,44).…”
Section: Discussionmentioning
confidence: 99%
“…In one series, ultrasonography wasn't attempted until the lung had been excluded from ventilation for at least 40 min (43). Also, there is a learning curve associated with use of the ultrasound equipment, with some studies reporting the presence of a radiologist in the operating room (38,43,44). Suggestion has been made that nodules can be diagnosed based on their ultrasonographic characteristics, but more work must be done in this area (41,45).…”
Section: Discussionmentioning
confidence: 99%
“…The number of patients included in these series is low (average <20 patients per study), with the highest being 35 patients in the study by Piolanti et al [53]. Interestingly, some authors employed this technique to localize pulmonary cancers and mediastinal structures (Table 1).…”
Section: Noninvasive Intraoperative Techniquesmentioning
confidence: 93%
“…Several perspective studies have shown that the intrathoracoscopic US technique is, in experienced hands, very sensitive and shows a good percentage of nodule localization, ranging from 70 to 100% [10,18,21,36,38,53,57,62,66,67,82]. The number of patients included in these series is low (average <20 patients per study), with the highest being 35 patients in the study by Piolanti et al [53].…”
Section: Noninvasive Intraoperative Techniquesmentioning
confidence: 94%
“…The use of ultrasonography for the localization of lung nodules has been reported since in the 1990s [1][2][3][4][5][6][7][8]. Although described in 1990s this technology has not been fully adapted to thoracic surgery.…”
Section: Introductionmentioning
confidence: 99%